A contribuição dos recursos estratégicos para a implantação da produção enxuta e para a vantagem competitiva em uma organização calçadista do estado da Paraíba - Silva, Alline Thamyres Claudino da (2014)
The main objective of this work is to analyze how strategic resources contribute to the implementation of lean production and to the obtaining competitive advantage in an organization that operates in the footwear sector in the state of Paraíba, from the perspective of the Resource-Based View. For this purpose, initially, literature review was elaborate based on the following topics: Strategy, Operations Strategy, Lean Production and Resource Based View. With the key concepts and contributions observed in the literature, it was possible to develop an analysis procedure that consists of five phases: detailing the operations strategy, identification of lean production practices, description of the trajectory of lean implementation, analysis of the relationship of resources and practices and, finally, evaluation of resources according to the theoretical assumptions of the RBV. The research is characterized as a case study, qualitative and descriptive nature. The main instruments to data collection were adopted: semistructured interviews, documents and direct observation. Through the case study, it was found that the most important resources for the implementation of lean production in the company are: labor, qualified people, machines, culture and labour training. Culture and labour training are resources that contribute significantly to the company's competitive advantage, because they are intangible, therefore are more difficult to be identify and copied by the competition, contributing to its high value and sustainability. In particular, the culture was well evaluated in relation to sustainability. This can be explained by the fact that this resource has a strong barrier against imitation and duplication, for example, it involves social complexity and causal ambiguity. Moreover, organizational culture, along with the labour training contributed to 14 of the 15 practices implemented by the organization studied. This evaluation indicated that the deployment trajectory of lean production in the organization was unique, because it is engrained in the history and organizational learning developed by the company over time